CENTRAL ASIAN STUDIES IN THE FRAMEWORK OF INTERNATIONAL RELATIONS THEORIES Interview with R.R. BURNASHEV, Professor of Kazakhstan-German University (Kazakhstan) - - - (Vestnik RUDN. International Relations, 2018)
Prof. Rustam Burnashev was born in 1969 in Tashkent. In 1986-1991 studied at the Philosophy and Economics Department of Tashkent State University named after V. Lenin on the specialty “Philosophy”. In 1995-1997 he studied in the graduate school of the Institute of Philosophy and Law named after M. Muminov of the Academy of Sciences of the Republic of Uzbekistan; PhD. Teaching career began in 1991 as a teacher of philosophy and logic of the Department of Philosophy and Law of the Second Tashkent Medical Institute. Since 1998 was Senior Research Fellow, then the head of the Foreign Policy Analysis sector of the Institute of Strategic and Interregional Studies under the President of the Republic of Uzbekistan. Since 2000 - Associate Professor of the Faculty of International Relations, Abylai Khan University of International Relations and World Languages. Since 2002 - Professor of the Faculty of Social Sciences of the Kazakh-German University. From 2004 to 2010 Prof. Burnashev regularly worked at the University of California-Berkeley as an invited researcher. In his interview, Prof. Burnashev analyzes the state of Central Asian studies in Europe and the US, talks about the specifics of the development of Central Asia at the present stage, emphasizing the far-fetched and exaggerated nature of the threat emanating from radical Islamist groups for the Central Asian region.